Analisis Hubungan Komplikasi Kehamilan Dengan Kejadian Bayi Berat Lahir Rendah di Indonesia (Analisis Data Sekunder Survei Demografi Kesehatan Indonesia Tahun 2017) - Maulidani Maulidani; Asnawi Abdullah; Nurjannah Nurjannah (STIKes Hang Tuah Pekanbaru, 2023)
Pregnancy complications are problems or health problems that often occur during pregnancy, and can impact not only the health of the mother but also the newborn. High risk during pregnancy occurs in pregnant women under the age of 19 and over 35 years and the length of marriage is over 5 years. Further analysis of this secondary data is descriptive of analytics conducted using a Cross-sectional design. Research sites throughout the Province in Indonesia, conducted from July 24 to September 30, 2019. The secondary data was re-processed by researchers with several different variables in 2019. The samples in this study were all SDKI 2017 samples that met the criteria of 16,343 samples. Then the data is analyzed with univariate analysis, bivariate with a chi-square test, and multivariate with a logistics regression test. The results of the univariate analysis found that the percentage of babies born with LBW was 7.53% and the proportion of respondents who had pregnancy complications was 87.96%. Then the bivariate analysis obtained that there is a relationship between pregnancy complications with the incidence of BBLR obtained a p-value of 0.025 or a value of 0.81. Later multivariate analysis showed that the most influential factors were birth distance with OR=1.12 and Antenatal Care services (ANC) with OR=1.22. Then the factors associated with causing LBW are complications, maternal age, and socioeconomic status with a p-value of <0.05. There is a link between pregnancy complications and LBW events with a p-value of 0.025. Pregnancy complications have a connection to the incidence of LBW, it is necessary for every pregnant woman to be able to increase knowledge of the danger signs of pregnancy.